Nanetto Pipetta : modos de representação - Perotti, Tania (My University, 2014)
This study has searched the comprehension about certain representation structures found in Aquiles Bernardi s (1937) work. Among the aspects which build up this representation, the cultural aspects had been analysed in order to be more specific, which doesn t exclude social and politic questions when necessary. It s about a route where, from the analyses and interpretation, i tried to understand how the Italian Immigration culture from Rio Grande do Sul changes happened from its real context to the limits concerning the fiction aspect present in the book which is this work s corpus. In this process i intended to comprehend in what way the Italian Immigration and the clergy culture were helpful to the analysed work, as well as the result of this conjugation.
Este estudo busca analisar determinados elementos de representação, presentes no Nanetto Pipetta de Aquiles Bernardi (1937). Entre eles, os aspectos culturais foram analisados de maneira mais detida, ao lado de questões sociais e políticas. A partir da análise e da interpretação, buscou-se compreender como aconteceu o trânsito da cultura da imigração italiana do Rio Grande do Sul de seu contexto real para os limites comportados pelo âmbito da ficção apresentados na obra. Nesse processo de transfiguração, buscou-se compreender de que maneira a cultura da imigração italiana e a cultura clerical colaboraram para que o texto literário analisado assumisse os contornos que o constituem, bem como qual o resultado dessa conjugação.
Keywords: Letras; Cultura popular; Cultura da imigração italiana; Cultura clerical; Aquiles Bernardi; Vita e storia de Nanetto Pipetta: nassuo in Itália e vegnudo in Mérica par catare la cucagna (Obra literária); Literatura vêneto-rio-grandense; Imigração italiana; Literatura; Representação; Popular culture; Italian immigration culture; Clergy culture; Aquiles Bernardi; Nanetto Pipetta; Literatura